A Phenomenological Study on the Intersections of High School Students’ Educational Trajectories in Different Types of High Schools in Turkey - Mustafa Sever; Burcu Çıldır; Ayşe Gülsüm Akçatepe (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this research, we examined the student practices of high school students in different types of high schools in Turkey in the light of Bourdieu's concepts of habitus and cultural capital. While tracing the essences of student practices with a phenomenological approach, we tried to make explicit what lies at the intersections of different types of high schools in terms of these practices and how the educational trajectories of students in these high schools are shaped and reshaped. We conducted the research in six different types of high schools in Ankara. Through a phenomenological analysis of in-depth interviews with 96 high school students and a total of seven mothers, we explored student practices and the interrelationships between habitus and cultural capital in the home and school environments. As a result of this analysis, we interpreted the essences that cut across the educational trajectories of students positioned in different types of high schools as living with the illusion of school choice, declaring the position with a sense of entitlement, engagement with cultural fields through cultural consumption habits, and utilizing sports for the presentation of self. The main result of the research shows that although students are positioned in different trajectories, the essence of their student practices does not change. We believe that this result should be explained from the perspective that the existence of different types of schools or different routes for students cannot guarantee the social mobility of individuals, but continues to serve the reproduction of all the historical and social contingencies that create these students' positionality.